Wild Edible Fruits of Fakim Wildlife Sanctuary, Nagaland, North-east India - , Rongsensashi; Mozhui, Renchumi; Changkija, Sapu; Limasenla (Indian Forester, 2013)
Fakim wildlife sanctuary is situated in the eastern part of Nagaland under Kipheri district bordering Myanmar. The sanctuary harbours rich floristic wealth of which many are fruit and medicinal plants.The present paper deals with wild edible fruits of Fakim wildlife sanctuary, Nagaland. A total of 45 wild edible fruits belonging to 26 families and 36 genera are documented in the present survey.